2012
DOI: 10.1111/j.1742-7843.2012.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

The Absorption Profile of Pregabalin in Chronic Pancreatitis

Abstract: It was recently shown that pregabalin decreased pain associated with chronic pancreatitis. It is well known that pancreatitis patients suffer from fat malabsorption with accompanying diarrhoea because of loss of exocrine pancreatic enzyme production. This may lead to changes in the mucosal surface in the small intestine and possibly affect the absorption of pregabalin. The pharmacokinetics of pregabalin has never been investigated in patients suffering from chronic pancreatitis. The aim of this study was to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, as pregabalin reach a steady state plasma concentration after maximal 48 hours, the analgesic effect would theoretically be constant throughout the day when administered two times daily [25]. This is supported by a recent publication where the pharmacokinetic profile of pregabalin was reported in patient with CP and found to be comparable to that of healthy subjects [26]. Also, patients were asked to report the average pain score for the last 24 hours and not the pain score at the time of registration.…”
Section: Discussionmentioning
confidence: 64%
“…However, as pregabalin reach a steady state plasma concentration after maximal 48 hours, the analgesic effect would theoretically be constant throughout the day when administered two times daily [25]. This is supported by a recent publication where the pharmacokinetic profile of pregabalin was reported in patient with CP and found to be comparable to that of healthy subjects [26]. Also, patients were asked to report the average pain score for the last 24 hours and not the pain score at the time of registration.…”
Section: Discussionmentioning
confidence: 64%
“…Pregabalin is rapidly absorbed in the fasting state, with peak plasma concentrations occurring within 1 h. Food reduces the absorption rate, resulting in lowered and delayed maximum plasma concentration without a clinically significant effect on the extent (bioavailability) 5. A few studies on the population PK of pregabalin have been conducted;68 these studies commonly employed a one-compartment model with first-order absorption and elimination only without mentioning any attempt to find a better model. However, in these studies, a common trend to underestimate pregabalin concentrations around the time of maximum plasma concentration (T max ) was observed, which suggests the possibility of an inappropriate choice of absorption model (first-order absorption).…”
Section: Introductionmentioning
confidence: 99%
“… 47 , 48 Besides, it was also confirmed by a population pharmacokinetic model that pregabalin had a well-absorption profile in patients with CP. 49 However, a systematic review published in 2016 by Cochrane Library which only included the study of Olesen et al in 2011 suggested that the relevant evidence of pregabalin administration in CP patients was of low-to-moderate quality because of the short-term period of the trial and more adverse events compared with placebo group. 50 …”
Section: Medicationmentioning
confidence: 99%